Assessment of Dim Mutants of the Vibrio harveyi species isolated from the Gulf of Mexico - (:unkn) unknown (My University, 2012)
Isolating environmental dim and dark mutants of V. harveyi gives insight into the positive selection and maintenance of lux genes in a natural setting. Mutants were isolated from Boca Ciega Bay, FL., on the basis of the presence of lux genes without visible luminescence when plated on SWC agar. Of 600 isolates, four mutants were found to glow minimally on X-ray film. Of these four, luminescence was rescued in three isolates to a varying degree by addition of aldehyde, a component of the bacterial luminescence reaction. These four lux operons were sequenced, and two were shown to have a frameshift in luxC, one had a transversion leading to a premature stop codon in luxA, while the final strain seemed to be intact. Lux operons from 186 and 500 were cloned into E. coli to assess luminescence outside of V. harveyi's quorum-sensing circuit and quantitative assays were done to ascertain whether the operon or upstream region were implicated in the reduced luminescence.